Analysis of the Results Athletes of the Test Reaction to a Moving Object - NuhadKhudhair Abbas AL-Rubaye (Indian Journal of Forensic Medicine & Toxicology, 2021)
The analysis of early and late feedback data for athletes on a moving object allows us to interpret the balancedata, the degree of equilibrium of excitement and inhibition in athletes in the experimental. When comparingthe number of leading and delayed reactions in players tested in the control group after an educationalexperience, it was found that in the majority (43.8%) the number of advances (early reactions) exceededthe number of delays. This fact indicates an imbalance in neurological processes with the predominanceof excitation force. At the same time, the number of athletes in this group, whose response was delayed,reached 37.5%, suggesting dysfunction of neurological processes, with the predominance of inhibition.Only 18.7% of athletes are diagnosed with equilibrium in neurological processes. The indices of the numberof delays and advances are approximately equal and differ slightly from each other (R> 0.05).